2022
DOI: 10.1111/ggi.14416
|View full text |Cite
|
Sign up to set email alerts
|

Trends in places and causes of death among centenarians in Japan from 2006 to 2016

Abstract: Aim Amid the global aging, an establishment of healthcare policies for the aged population is a common issue to be addressed. However, few studies on centenarians have reported place and cause of death (PoD and CoD, respectively) as indicators of end‐of‐life care quality. This study aimed to analyze trends in PoD and CoD among centenarians in Japan. Methods Data from death certificates from Japanese vital statistics were analyzed; 205 513 deaths occurred among centenarians (aged ≥100 years) in Japan during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…[21] Another study also showed that centenarians had higher proportion of home death (92.8%) than that of elderly people aged 90–99 years (91.6%) and those aged 80–89 years (86.3%). [22] Moreover, a similar proportion of centenarians' deaths in their own homes (63.8%) in Taiwan province of China, [6] which has a common cultural background, also supports this hypothesis. Therefore, although the prevalence of nursing homes as PoDs increased consistently from 2014 to 2020 and relatively high proportions of centenarians dying in the hospital were observed in Shanghai (39.38%) and Beijing (39.28%), it may still take many years for China as a whole to achieve a shift in the pattern of PoD toward that in Japan characterized by higher numbers of hospital deaths or England characterized by higher numbers of deaths in nursing homes.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…[21] Another study also showed that centenarians had higher proportion of home death (92.8%) than that of elderly people aged 90–99 years (91.6%) and those aged 80–89 years (86.3%). [22] Moreover, a similar proportion of centenarians' deaths in their own homes (63.8%) in Taiwan province of China, [6] which has a common cultural background, also supports this hypothesis. Therefore, although the prevalence of nursing homes as PoDs increased consistently from 2014 to 2020 and relatively high proportions of centenarians dying in the hospital were observed in Shanghai (39.38%) and Beijing (39.28%), it may still take many years for China as a whole to achieve a shift in the pattern of PoD toward that in Japan characterized by higher numbers of hospital deaths or England characterized by higher numbers of deaths in nursing homes.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding the PoD, more than 80% of Chinese centenarians died in their homes between 2013 and 2020, which was higher than the corresponding proportion for the whole population in the same period, approximately 73% [Supplementary [5] In Japan, 58.47% of centenarians died in the hospital, 25.59% of them died in nursing homes, and only approximately 15% of them died in their own homes. [6] This difference in PoD may be related to the degree of population aging, socioeconomic status, and the accessibility of medical and health resources across these countries. However, it may also be related to traditional Chinese culture, in which elderly people generally prefer to die in a home environment rather than a clinical environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations